2011
DOI: 10.1007/s10096-011-1462-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various cytokines elicited during antigen-specific recall as potential risk indicators for the differential development of leprosy

Abstract: Leprosy is a dermato-neurological disease caused by Mycobacterium leprae infection that manifests across a wide range of clinical and immunological outcomes. Diagnosis is still currently based on clinical manifestations and simple tests are needed. This study investigated whether biomarkers induced by defined M. leprae proteins in 24-h whole blood assays (WBA) could discriminate active leprosy patients from at-risk contacts. Newly diagnosed, untreated paucibacillary (PB; tuberculoid leprosy/borderline tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…This has been confirmed by the observation that polymorphisms of key cytokines genes, such as TNF (Santos et al 2002; Sapkota et al, 2010; Cardoso et al 2011), IL-12 (Alvarado-Navarro et al 2008), IL-4 (Yang et al 2011; Sampaio et al 2012), IL-10, TGF-B, IL-6, and their respective receptors (Aggarwal et al 2011) have been associated with susceptibility to and severity of leprosy.…”
Section: Introductionmentioning
confidence: 84%
“…This has been confirmed by the observation that polymorphisms of key cytokines genes, such as TNF (Santos et al 2002; Sapkota et al, 2010; Cardoso et al 2011), IL-12 (Alvarado-Navarro et al 2008), IL-4 (Yang et al 2011; Sampaio et al 2012), IL-10, TGF-B, IL-6, and their respective receptors (Aggarwal et al 2011) have been associated with susceptibility to and severity of leprosy.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, we observed that these same antigens promote interleukin (IL)-4 or IL-5 secretion in whole blood assays using lepromatous patient blood. Furthermore, we identified an HHC who responded similarly to MB patients (Sampaio et al 2011a) (Fig. 1C), although it remains unclear whether this individual is developing clinical signs.…”
Section: Resultsmentioning
confidence: 88%
“…Detection of a cellmediated response against Mycobacterium tuberculosis (Mtb) antigens is the preferred evidence for diagnosis of tuberculosis, either through intradermal injection of purified protein derivative testing or more recently, by ex vivo recall (QuantiFERON tests, Cellestis, Melbourne, Australia) (Mazurek & Villarino 2003, Connell et al 2006). We and others have identified various M. leprae antigens that elicit interferon (IFN)-γ secretion from T-cells of tuberculoid leprosy patients, but do not cross react with cells from individuals exposed to BCG or Mtb (Spencer et al 2005, Duthie et al 2008, Geluk et al 2008, 2011, Sampaio et al 2011a. The majority of healthy household contacts (HHC) of MB patients respond in a manner quantitatively and qualitatively comparable to PB patients; however, this is likely indicative of exposure or asymptomatic infection and is a poor diagnostic method for PB disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utah residents who are graduates of a NICU and who meet any the following criteria are eligible for enrollment: 1) birth weight ≤1250 grams, 2) gestational age of ≤ 26 weeks, 3) hypoxic ischemic encephalopathy 10 , 4) extracorporeal membrane oxygenation (ECMO). UDOH data suggest that approximately 50% of eligible preterm infants born in the State of Utah are seen in the Utah NFP (unpublished data).…”
Section: Methodsmentioning
confidence: 99%